The oil curse : how petroleum wealth shapes the development of nations - Ross, Michael Lewin, 1961- (Book collections on Project MUSE., 2012)
Countries that are rich in petroleum have less democracy, less economic stability, and more frequent civil wars than countries without oil. What explains this oil curse? And can it be fixed? In this groundbreaking analysis, Michael L. Ross looks at how developing nations are shaped by their mineral wealth--and how they can turn oil from a curse into a blessing. Ross traces the oil curse to the upheaval of the 1970s, when oil prices soared and governments across the developing world seized control of their countries' oil industries.